Use of collaborative learning approach for increased cure rate among children aged 6–59 months with severe wasting in Karamoja, Uganda. Issue 1 (10th February 2023) - Mokori, Alex; Ndungutse, Amos Hashaka; Amongin, Dinah; Agabiirwe, Caroline Noel; Byabasheija, Robert; Draru, Joyce
Abstract : Background: At 10%, Karamoja region has the highest rate of child wasting in Uganda. The region has 126 outpatient therapeutic care (OTC) sites for managing children with severe acute malnutrition. Local problem: Cure rate (CR) in OTC in Karamoja remains below the international standard of over 75%. The study aimed at increasing the CR in 10 OTC sites in Karamoja, from 74.1% to >75% in 13 months. Methods: The study commenced in July 2018, up to September 2019, in purposively selected health facilities in six districts in Karamoja. Quality improvement (QI) methods per the Ministry of Health QI Framework were applied. QI teams (QITs) tracked the outcome of the tested changes for 13 months. χ 2 tests were used to assess the intrafacility and interdistrict association in CR. Intervention: Institute for Health Improvement (IHI) (2003) improvement model was applied in this collaborative. QITs conducted root cause analysis of CR gaps, which guided them in the development of improvement aims, changes and indicators. QITs used plan–do–study–act cycles to test and adopt the feasible changes. Results: CR increased from 74.1% to 78.6%, with an overall average of 80% within 13 months. Abim district had the highest CR (83.3%) and Kaabong district the lowest (75.2%). Health centre II (84.0%) had the highest CR. Assigning village health teams to follow up caregivers of children in OTC with missed appointments, allocation of village health teams and local leaders to monitor the administration of ready-to-use therapeutic food to children, and screening and treating comorbidities among children in OTC increased CR. Conclusions: QI methods focusing on collaborative learning increased CR among children in OTC in Karamoja. Sustaining the gains requires district health offices, partners and health facility management's commitment to institutionalise the QI collaborative learning approaches.